2020
DOI: 10.3389/fpls.2019.01668
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Loci Through Genome-Wide Association Studies to Improve Tolerance to Sulfur Deficiency in Rice

Abstract: Sulfur (S) is an essential nutrient for plant growth and development; however, S supply for crop production is decreasing due to reduced inputs from atmospheric deposition and reduced application of S-containing fertilizers. Sulfur deficiency in soil is therefore becoming a widespread cause of reduced grain yield and quality in rice (Oryza sativa L). We therefore assessed the genotypic variation for tolerance to S deficiency in rice and identified loci associated with improved tolerance. Plants were grown in n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…The model was run using an in-house R script and the rrBLUP package returned a quantile-quantile plot and a Manhattan plot with a significant threshold set to a 5% FDR (false discovery rate) [ 20 , 23 ]. Loci were considered significantly associated with a trait based on a threshold of–log(10)(p) > 5 for those peaks characterized by at least three consecutives Quantitative Trait Nucleotide (QTN) [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The model was run using an in-house R script and the rrBLUP package returned a quantile-quantile plot and a Manhattan plot with a significant threshold set to a 5% FDR (false discovery rate) [ 20 , 23 ]. Loci were considered significantly associated with a trait based on a threshold of–log(10)(p) > 5 for those peaks characterized by at least three consecutives Quantitative Trait Nucleotide (QTN) [ 19 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…For the purpose of confirming detected associations, a second analysis was conducted with the software program Trait Analysis by association, Evolution and Linkage 5.0 (TASSEL) [ 25 ]. Prior to association analysis, the 404K coreset SNP genotype dataset was filtered as follows: heterozygotes and indels were set as missing values, and SNP having more than 5% missing data or minor allele frequency (MAF) below 0.03 were excluded [ 19 ]. The association mapping was then analyzed using the mixed linear model (MLM) procedure, with three principal components (PCA) and a kinship matrix.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GWAS studies for root morphological traits in rice were reviewed (Bettembourg et al 2017;Biscarini et al 2016;Courtois et al 2013;Kadam et al 2017;Li et al 2017;Mai et al 2020;Pariasca-Tanaka et al 2020;Phung et al 2016;Wang et al 2018;Xu et al 2020), and the reported SNP peak positions were collected to find the overlaps between their positions with MQTLs. The genes located in the SNP peak positions (+/-25 kb) were extracted from Oryza sativa Japonica group (IRGSP-1.0) reference genome according to their physical positions.…”
Section: Collecting Rsa Related Genome-wide Association Studies (Gwas) and Comparing With Mqtlsmentioning
confidence: 99%
“…Biofortification using molecular plant breeding approaches has also been undertaken to address the issues of malnutrition and ensure nutrition and food security (Calayugan et al., 2020). To this end, efforts are made for producing crops with enhanced nutritional values by identifying quantitative trait loci (QTLs) using the traditional QTL mapping approach (Calayugan et al., 2020; Jeong et al., 2020), or by employing the genome wide association studies (GWAS) for identifying high value genes for enriched minerals and vitamins in grains (Lopes et al., 2015; Pariasca‐Tanaka et al., 2020). Crops, such as pearl millet ( Cenchrus americanus ) with enriched Fe, maize ( Zea mays ), and rice ( Oryza sativa ) with increased vitamin A, wheat ( Triticum aestivum ), and rice varieties with elevated grain Zn, have been developed through biofortification approaches using biotechnological and breeding approaches to address nutritional security (Bouis & Saltzman, 2017).…”
Section: Introductionmentioning
confidence: 99%